Synthesis, biological characterization and evaluation of molecular mechanisms of novel copper complexes as anticancer agents - Acilan, Ceyda; Cevatemre, Buse; Adiguzel, Zelal; Karakas, Didem; Ulukaya, Engin; Ribeiro, Nádia; Correia, Isabel; Pessoa, João Costa (Biochimica et biophysica acta. General subjects, 2017)
To overcome the hurdles of cisplatin, majorly its toxicity and resistance, there has been extensive search for alternative anti-cancer metal-based compounds. Here, three Cu(II)-complexes, Cu(Sal-Gly)(phen), Cu(Sal-Gly)(pheamine), Cu(Sal-Gly)(phepoxy) are characterized for their interaction with DNA, cytotoxicity and mechanism of action. The binding ability of the complexes to Calf-Thymus DNA was evaluated by competition fluorescence studies with thiazole-orange, UV–Vis and circular dichroism spectroscopic titrations. Cytotoxicity was evaluated by MTT analysis. The DNA damage was analyzed through cleavage of supercoiled DNA via agarose gel-electrophoresis, and 8-oxo-guanidine and ɣH2AX staining in cells. Apoptosis was detected via DNA condensation/fragmentation, mitochondrial membrane potential, Annexin V staining and caspase 3/7 activity. Formation of reactive oxygen species was determined by DCFDA- and GSSG/GSH-analysis. Binding constants to DNA were evaluated as 1.7×106 (Cu(Sal-Gly)(phen)), 2.5×106 (Cu(Sal-Gly)(pheamine)) and 3.2×105 (Cu(Sal-Gly)(phepoxy)). All compounds induced DNA damage. Apoptosis was the main form of cell death. There was an increase in ROS, which is most likely responsible for the observed DNA-damage. Although the compounds were cytotoxic to all tested cancer cell lines, only Cu(Sal-Gly)(pheamine) displayed significantly lower toxicity towards non-cancer cells, its associated phenotypes differing from the other two Cu-complexes. Thus, Cu(Sal-Gly)(pheamine) was further assayed for molecular changes in response to drug treatment using a custom designed RT-qPCR array. Results showed that Harakiri was significantly upregulated. Presence of p53 was not required for apoptosis in response to Cu-complexes. These Cu-complexes, namely Cu(Sal-Gly)(pheamine), may be considered promising anticancer agents with activity in cancer cells even with deficient p53 status. [Display omitted] •Three copper(II) complexes are synthesized and characterized.•Cu(Sal-Gly)(pheamine) is the most specific complex towards cancer cells.•The main mechanism of cell death is apoptosis.•All complexes bind to DNA and induce oxidative damage.•Harakiri is significantly upregulated in response to Cu(Sal-Gly)(pheamine).